Partisipasi Pengguna Internet Indonesia dalam Pemanfaatan LAPOR! sebagai Layanan Pengaduan Publik - Muttaqin, Moh; Pusvita, Vita; Pangaribuan, Tristania; Simatupang, Oktolina (Jurnal Pekommas, 2024)
The People's Online Aspiration and Complaints Service (LAPOR!) was organized as an effort to increase public participation in government administration. LAPOR! is developing quickly, integrated with many central and regional government agencies; and it is officially designated as a general application for public complaint service in Electronic-Based Government System (SPBE). However, with the support of internet-based digital channels, the dominant access channels for LAPOR! users, it is not yet known how the public will participate in using LAPOR! as a public complaint service in various regions in Indonesia. This research aims to reveal the public participation of internet users according to provinces throughout Indonesia, by measuring the participation ratio as a basis for determining the level of participation in each province. Referring to the average national participation ratio (0.277), the research identified 15 provinces with high participation rates and 19 provinces with low participation rates. Among the provinces with high participation rates, five provinces meet the criteria for dominant participation rates, namely DKI Jakarta, South Kalimantan, Banten, DI Yogyakarta, and Central Kalimantan.